ANALISIS INSTRUMEN ASSESMEN : VALIDITAS, RELIABILITAS, TINGKAT KESUKARAN DAN DAYA BEDA BUTIR SOAL - Hera Apriliana Saputri Saputri; Zulhijrah; Nabila Joti Larasati; Shaleh (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to analyze the assessment instrument, focusing on the validity, reliability, difficulty level, and differentiation of the items. The validity of the instrument was evaluated to measure the extent to which the instrument measured what it was supposed to measure. Reliability was tested to assess the level of consistency of the measurement results of the instrument. In addition, the level of difficulty of the items was analyzed to determine how difficult or easy the questions posed to the participants were. Meanwhile, item discrimination was assessed to determine the extent to which items were able to differentiate between participants who had different levels of ability. The research method involves collecting data from assessment instruments used in a particular context. The results of the data analysis illustrate the validity of the instrument, the reliability of the measurement, as well as the characteristics of the difficulty level and the differentiability of the items. The findings of this study provide deep insights into the quality of assessment instruments used in a particular context, with important implications for the improvement and development of future evaluation instruments. This research is expected to make a positive contribution to improving the quality of measurement in the context of assessment, and can be a reference for the development of evaluation instruments in various fields. Keyword: Assessment, Differentiating Power, Reliability, Difficulty, Validity